Developments in surface contamination and cleaning. Volume 1, - Kohli, Rajiv; Mittal, K. L., 1945- (Developments in surface contamination and cleaning ;, 2016)
Developments in Surface Contamination and Cleaning, Vol. 1: Fundamentals and Applied Aspects, Second Edition, provides an excellent source of information on alternative cleaning techniques and methods for characterization of surface contamination and validation. Each volume in this series contains a particular topical focus, covering the key techniques and recent developments in the area. This volume forms the heart of the series, covering the fundamentals and application aspects, characterization of surface contaminants, and methods for removal of surface contamination. In addition, new cleaning techniques effective at smaller scales are considered and employed for removal where conventional cleaning techniques fail, along with new cleaning techniques for molecular contaminants. The Volume is edited by the leading experts in small particle surface contamination and cleaning, providing an invaluable reference for researchers and engineers in R & D, manufacturing, quality control, and procurement specification in a multitude of industries such as aerospace, automotive, biomedical, defense, energy, manufacturing, microelectronics, optics and xerography.